Respuesta :
Answer: C
Step-by-step explanation: With inverse equations, you switch y and x (y=f(x)) and undo/reverse the steps towards x.
1. Multiply by 3
2. Add 2
Equation by itself
0. x
1. 3(x)
2. 3(x+2)
The inverse of the given function is f⁻¹(x) = 3(x + 2).
What is the inverse of a function?
The inverse function of a function f(x) in mathematics is a function that reverses the operation of f(x).
The given function in the question:
f(x) = (x/3) - 2
f(x) + 2 = x/3
x + 2 = f⁻¹(x)/3
f⁻¹(x) = 3(x + 2)
Hence, the inverse of the given function is f⁻¹(x) = 3(x + 2).
Learn more about inverse on:
https://brainly.com/question/3831584
#SPJ2